2019
DOI: 10.1039/c9nj00275h
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction in the optical band-gap and defect assisted magnetic response in Fe-doped anatase TiO2nanocrystals as dilute magnetic semiconductors

Abstract: The nature of BMPs, whether overlapped or isolated, determines the magnetic behavior of Fe-doped TiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Fig. 7b 2P1/2) [67][68][69]. The contribution of oxygen in the XPS spectrum can be understood by the de-convoluted O1S peak, shown in Fig.…”
Section: Chemical Compositionmentioning
confidence: 92%
“…Fig. 7b 2P1/2) [67][68][69]. The contribution of oxygen in the XPS spectrum can be understood by the de-convoluted O1S peak, shown in Fig.…”
Section: Chemical Compositionmentioning
confidence: 92%
“…The emission peak at 468 nm, equivalent to 2.65 eV, is attributed to the surface oxygen vacancies and defects ( Akshay et al, 2019b ; Rathore et al, 2021 ). While the peak at 484 nm is due to the blue-green emission band that is attributed to the de-excitation to acceptor surface defects ( Prajapati et al, 2017 ; Akshay et al, 2019a ), the peak at 491 nm is due to the charge transition associated with oxygen defects ( Choudhury and Choudhury, 2014 ). Among the observed peaks, the peak at 468 nm of surface oxygen vacancies and defects accounted for the AHL detection, due to its prominence over the other peaks.…”
Section: Resultsmentioning
confidence: 99%
“…The estimated band gap of pristine TiO2 was found to be 3.50 eV, whereas the band-gap of Cu/TiO2_500, Cu/TiO2_650, Cu/TiO2_800 and Cu/TiO2_950 is 3.24 eV, 3.21 eV, 3.06 and 3.06 eV, respectively. One plausible explanation for the bandgap narrowing could be the presence of Tii defects in TiO2 NCs [41]. It is reported that the formation of Tii is generally due to the preparation conditions and annealing under air [42].…”
Section: Uv-visible Analysismentioning
confidence: 99%